Organizational and Economic Mechanism of Fertilizer Application Technology Management as a Basis for Region’s Progressive Development - BONDARENKO, Anatoly M.; LIPKOVICH, Edward I.; KACHANOVA, Ludmila S.; GLECHIKOVA, Natalia A.; SEREGIN, Aleksandr A. (Journal of Environmental Management and Tourism; Vol 8 No 5 (2017): JEMT Volume VIII Issue 5(21) Fall 2017DO - 10.14505//jemt.v8.5(21).13, 2018)
Relevance of the present paper stems from the necessity of harmonious interrelation between economy and society with due regard to economy branches’ development and compliance with environment protection policy. The goal of the research is the formation of Organizational and economic mechanism of organic fertilizers’ production and application technological processes management in the agricultural sector with grounding of strategic and tactic aspects. The main method of the problem resolution is represented with analysis and specification of theoretical provisions linked to technological processes’ management. We have developed methodology for formation of organizational and economic mechanism of fertilizer application. As a result, the elements of the mechanism, which include resource and product model, multicriterion model for choosing production and fertilizer application technologies, model for planning of additional income from the application, have been differentiated by tactic and strategic management levels. Their implementation will provide an increase in the gross yield of basic crops and their cultivation profitability, which is the basis for progressive development of region.